A NATURAL APPROACH TO RIVER ENGINEERING PRACTICE. A CASE STUDY OF THE LJILJANSKA RIVER - Jelena Marković Branković; Milica Marković; Aleksandar Kostić (Facta Universitatis. Series: Architecture and Civil Engineering, 2021)
In the past 30 years the efforts to protect river beds and banks have increased significantly. The selection and design of proper structural solution means finding a solution in accordance with construction principles, river geomorphology, avoiding channel aggradation, bed scour, bank erosion, resulting structure failure and significant harm to the stream and nearby property. On the other hand, the structure should be environmentally-friendly. Hydraulic structures generally have a strong impact on the environment, so providing “the right solution” presents a real challenge to engineers.